Prohibitions in the meta-inflammatory response: a review - Todosenko, Natalia; Yurova, Kristina; Vulf, Maria; Khaziakhmatova, Olga; Litvinova, Larisa (Frontiers in Molecular Biosciences, 2024)
Prohibitins are the central regulatory element of cellular homeostasis, especially by modulating the response at different levels: Nucleus, mitochondria and membranes. Their localization and interaction with various proteins, homons, transcription and nuclear factors, and mtDNA indicate the globality and complexity of their pleiotropic properties, which remain to be investigated. A more detailed deciphering of cellular metabolism in relation to prohibitins under normal conditions and in various metabolic diseases will allow us to understand the precise role of prohibitins in the signaling cascades of PI3K/Akt, Raf/MAP/ERK, STAT3, p53, and others and to fathom their mutual influence. A valuable research perspective is to investigate the role of prohibitins in the molecular and cellular interactions between the two major players in the pathogenesis of obesity—adipocytes and macrophages - that form the basis of the meta-inflammatory response. Investigating the subtle intercellular communication and molecular cascades triggered in these cells will allow us to propose new therapeutic strategies to eliminate persistent inflammation, taking into account novel molecular genetic approaches to activate/inactivate prohibitins.